Optimization of reaction conditions by detailed cycle simulation of thermo-chemical air separation for high-purity nitrogen production using the perovskite oxide SrFeO3 - Katrin Klingel; Lena Klaas; Nicole Neumann; Mathias Pein; Martin Roeb; Christian Sattler (Chemical Engineering Journal, 2026)

EEG-based assessment of sustained attention in geriatric inpatients: a feasibility study - Lina Stagneth; Johanna Geritz; Gesine Hermann; Lea Dahl; Leoni Zuber; Christian Neumann; Josephine Lassen; Corina Maetzler; Cornelia Kranczioch; Julius Welzel; Walter Maetzler (GeroScience, 2026)
Sustained attention is a core cognitive function, frequently declines with age and neurological disease, and is highly relevant for functional outcomes in geriatric populations. Electroencephalography (EEG) offers high temporal resolution for assessing attentional processes, but its feasibility in multimorbid geriatric inpatients remains insufficiently characterized. This study evaluated the procedural and methodological feasibility of EEG-based sustained-attention assessments in geriatric inpatients undergoing early rehabilitative geriatric complex treatment (ERGCT). Geriatric participants completed standardized neuropsychological testing and two computerized attention tasks, the Psychomotor Vigilance Task (PVT) and a cued Go-NoGo task, during 32-channel EEG recording, including a resting-state recording. Feasibility was assessed using procedural indicators (recruitment, task completion, follow-up participation) and methodological indicators of EEG data quality, specifically the signal-to-noise ratios (SNR) and identification of expected event-related potential (ERP) components (P100, P300). Of 173 patients referred to the ERGCT programme, 43 could be included. Of those, 38 could undergo structured cognitive testing, and resting-state EEG and task-evoked ERPs could be recorded with adequate signal quality However, procedural feasibility was limited by substantial selection and attrition, resulting in incomplete protocol completion. Exploratory analyses suggest an association between higher resting-state alpha-band signal quality and faster PVT reaction times, whereas no associations were observed with global cognition, executive function, or age. Overall, resting-state and task EEG measures of sustained attention could be acquired with adequate data quality only in a selected subgroup of geriatric inpatients, who were able to participate in structured cognitive assessments, while extended and repeated assessment protocols were constrained by procedural burden, suggesting that EEG-based follow-up assessments are difficult to implement under current clinical conditions.

A new genus and species of Galeritidae (Echinoidea, Echinoneoida) from the Upper Campanian (Cretaceous) of N Germany - Christian Neumann; Manfred Kutscher (PalZ, 2026)
A new genus and species of Cretaceous echinoneoid echinoid, Catinogalerus alexanderi gen. et sp. nov., is described and illustrated on the basis of 27 specimens originating from the Late Campanian of Kronsmoor and Rügen (both northern Germany). Morphologically, the new taxon appears closest to Galerites which it resembles in many aspects. The concave, saucer-shaped apical region, and cone-shaped protrusions of the genital plates are unique characters differentiating C. alexanderi from all other galeritids. Additional distinguishing characters comprise the adoral plate architecture with numerous small ambulacral plates combined with strongly offset pore pairs close to the peristome.

Simulating Central-European forests in the 21st century. Effects of climate change, disturbances and management on stocks, productivity and harvests - Manfred J. Lexer; Christoph Pucher; Christian Hochauer; Mathias Neumann; Herbert Formayer; Kristoffer Hasel (Journal of Environmental Management, 2026)

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

First subfossil Holocene avian breeding burrows in volcanic rocks of the Tibesti Mountains (Chad) - Jens Hering; Heidi Hering; Martin Winter; Stefan Kröpelin; Peter H. Barthel; Christian Neumann (Journal of Ornithology, 2025)

Driving a Circular Economy: Nudging and Innovative Strategies for Promoting Post-Consumer Recycled Plastic Home-Appliances - Nikolas Neumann; Aline Mangold; Julia Schneider; Christian Wölfel (Circular Economy and Sustainability, 2025)
The various social and ecological crises of our time are leading to ever louder calls for a sustainable transition towards a sustainable circular economy. As a result, the recycling of plastics is increasingly being brought to the foreground and the increased use of post-consumer recyclate (PCR) is being called for. However, the acceptance of products made from PCR plastic and how this can be increased is still largely unclear. This study uses a light switch to investigate the purchase intention and willingness to pay for household appliances made of (supposed) PCR plastic and how this can be increased with the help of nudges and guideline-based cues. In addition, the influence of a sustainability attitude is examined. An experimental study using a single-factor between-subjects study design ( n = 90) with six different cues has been conducted. A light switch made of (supposed) PCR plastic was used as a stimulus. The study results indicate that the purchase intention for PCR-based household appliances can be significantly increased using specific informational cues. Of the five cues tested, only one (innovation) did not lead to a significant increase in purchase intention when compared to the baseline cue. Contrary, none of the five cues led to a significant increase in willingness to pay when compared to the baseline cue. No significant moderating effect of sustainability attitude was found in either case. Possible explanations for these results are the attitude-behavior-intention gap and the influence of perceived aesthetics.

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

TGFβ signalling pathway impacts brain metastases profiles in locally advanced colorectal cancer - Sven Jacob; Ilja Balonov; Vindi Jurinovic; Christian Heiliger; Tengis Tschaidse; Jörg Kumbrink; Thomas Kirchner; Jens Werner; Martin K. Angele; Marlies Michl; Jens Neumann (Clinical & Experimental Metastasis, 2024)
Rationale Colorectal Cancer (CRC) represents the third most common type of cancer in Germany and the second most common cancer-related cause of death worldwide. Distant metastases are still the main limit for patient survival. While liver metastases as well as peritoneal carcinomatosis can often either be resected or treated with systemic therapy, little options remain for brain metastases. Additionally, a number of studies has already investigated hepatic, peritoneal, pulmonary as well as continuing distant metastases in colorectal cancer. Yet, with respect to tumor biology and brain metastases, little is known so far. Material and methods Two cohorts, M0 without distant spread and BRA with brain metastases were build. RNA was isolated from paraffin embedded specimen. Gene expression was performed by an RNA NanoString-Analysis using the nCounter® PanCancer Progression Panel by NanoString-Technologies (Hamburg, Germany). Results were analysed by principal component analysis, gene expression and pathway analysis using commonly available databases such as KEGG as benchmark for comparison. Results We were able to determine a gene signature that provides a sophisticated group separation between M0 and BRA using principal component analysis. All genes with strong loading characteristics on principal component 1 were cross-referenced with the subsequently performed accurate gene set enrichment analysis (GSEA). The GSEA revealed a clear dysregulation of the TGFβ pathway in compared cohorts M0 and BRA. Interestingly, the targeted pathways analysis of the identified genes confirmed that in fact almost all strong loading genes of PC1 play a role in the TGFβ pathway. Conclusion Our results suggest the TGFβ pathway as a crucial player in the development of brain metastases in primary CRC. In some types of colorectal cancer, downregulation of the TGFβ pathway might hinder primary colorectal cancer to metastasize to the nervous system. While the paradoxical functioning of the TGFβ pathway is still not fully understood, these shed light on yet another clinical implication of this complex pathway.

SIMULATeQCD: A simple multi-GPU lattice code for QCD calculations - Lukas Mazur; Dennis Bollweg; David A. Clarke; Luis Altenkort; Olaf Kaczmarek; Rasmus Larsen; Hai-Tao Shu; Jishnu Goswami; Philipp Scior; Hauke Sandmeyer; Marius Neumann; Henrik Dick; et al. (Computer Physics Communications, 2024)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Canonical circuit computations for computer vision - Daniel Schmid; Christian Jarvers; Heiko Neumann (Biological Cybernetics, 2023)
Advanced computer vision mechanisms have been inspired by neuroscientific findings. However, with the focus on improving benchmark achievements, technical solutions have been shaped by application and engineering constraints. This includes the training of neural networks which led to the development of feature detectors optimally suited to the application domain. However, the limitations of such approaches motivate the need to identify computational principles, or motifs, in biological vision that can enable further foundational advances in machine vision. We propose to utilize structural and functional principles of neural systems that have been largely overlooked. They potentially provide new inspirations for computer vision mechanisms and models. Recurrent feedforward, lateral, and feedback interactions characterize general principles underlying processing in mammals. We derive a formal specification of core computational motifs that utilize these principles. These are combined to define model mechanisms for visual shape and motion processing. We demonstrate how such a framework can be adopted to run on neuromorphic brain-inspired hardware platforms and can be extended to automatically adapt to environment statistics. We argue that the identified principles and their formalization inspires sophisticated computational mechanisms with improved explanatory scope. These and other elaborated, biologically inspired models can be employed to design computer vision solutions for different tasks and they can be used to advance neural network architectures of learning.

Effects of omecamtiv mecarbil and mavacamten in isolated human atrium - Lina Maria Rayo Abella; Christian Höhm; Britt Hofmann; Ulrich Gergs; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Heart failure is a syndrome that can result from impaired heart muscle contractions like in dilative cardiomyopathy but also from hypertrophic obstructive cardiomyopathy (HOCOM). A pharmacological therapy might lie in Ca 2+ -sensitizing or Ca 2+ -desensitizing drugs, respectively. Such drugs are thought to be omecamtiv mecarbil (OME) and mavacamten (MYK-461), respectively. Their function in contracting human muscle is not fully understood and was the focus of the present study. OME from 1 nM to 10 µM cumulatively applied failed to raise force of contraction in human right atrial preparations strips (HAP) or mouse left atrial preparations (LA). However, OME prolonged time to peak tension and time of relaxation in HAP and LA but did not alter the beating rate in right atrial preparations from mice (RA). In contrast, MYK-461 (10 nM to 10 µM) reduced concentration- and time-dependently force of contraction in HAP and LA. MYK-461 (10 µM) did not affect the beating rate in RA. In summary, the present data failed to detect an increase in force of contraction for OME, in human and mouse atrium. In contrast, a Ca 2+ desensitizer studied for comparison was able to reduce force of contraction in HAP and LA. We conclude that putative beneficial effects of OME in dilated cardiomyopathy cannot be explained by positive inotropic effects in the HAP, whereas beneficial functional effects of MYK-461 in HOCOM can be explained by negative inotropic effects in HAP.

Cardiac effects of ephedrine, norephedrine, mescaline, and 3,4-methylenedioxymethamphetamine (MDMA) in mouse and human atrial preparations - Joachim Neumann; Karyna Azatsian; Christian Höhm; Britt Hofmann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
The use of recreational drugs like ephedrine, norephedrine, 3,4-methylenedioxymethamphetamine (MDMA), and mescaline can lead to intoxication and, at worst, to death. One reason for a fatal course of intoxication with these drugs might lie in cardiac arrhythmias. To the best of our knowledge, their inotropic effects have not yet been studied in isolated human cardiac preparations. Therefore, we measured inotropic effects of the hallucinogenic drugs ephedrine, norephedrine, mescaline, and MDMA in isolated mouse left atrial (mLA) and right atrial (mRA) preparations as well as in human right atrial (hRA) preparations obtained during cardiac surgery. Under these experimental conditions, ephedrine, norephedrine, and MDMA increased force of contraction (mLA, hRA) and beating rate (mRA) in a time- and concentration-dependent way, starting at 1–3 µM but these drugs were less effective than isoprenaline. Mescaline alone or in the presence of phosphodiesterase inhibitors did not increase force in mLA or hRA. The positive inotropic effects of ephedrine, norephedrine, or MDMA were accompanied by increases in the rate of tension and relaxation and by shortening of time of relaxation and, moreover, by an augmented phosphorylation state of the inhibitory subunit of troponin in hRA. All effects were greatly attenuated by cocaine (10 µM) or propranolol (10 µM) treatment. In summary, the hallucinogenic drugs ephedrine, norephedrine, and MDMA, but not mescaline, increased force of contraction and increased protein phosphorylation presumably, in part, by a release of noradrenaline in isolated human atrial preparations and thus can be regarded as indirect sympathomimetic drugs in the human atrium.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Phosphodiesterases 2, 3 and 4 can decrease cardiac effects of H2-histamine-receptor activation in isolated atria of transgenic mice - Joachim Neumann; Rafaela Voss; Ulrich Laufs; Christian Werner; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
Histamine exerts cAMP-dependent positive inotropic effects (PIE) and positive chronotropic effects (PCE) on isolated left and right atria, respectively, of transgenic mice which overexpress the human H 2 -receptor in the heart (=H 2 -TG). To determine whether these effects are antagonized by phosphodiesterases (PDEs), contractile studies were done in isolated left and right atrial preparations of H 2 -TG. The contractile effects of histamine were tested in the additional presence of the PDE-inhibitors erythro -9-(2-hydroxy-3-nonyl)adenine hydrochloride (EHNA, 1 μM, PDE2-inhibitor) or cilostamide (1 μM, PDE3-inhibitor), rolipram (10 μM, a PDE4-inhibitor), and their combinations. Cilostamide (1 μM) and EHNA (1 μM), rolipram (1 μM), and EHNA (1 μM) and the combination of rolipram (0.1 μM) and cilostamide (1 μM) each increased the potency of histamine to elevate the force of contraction (FOC) in H 2 -TG. Cilostamide (1 μM) and rolipram (10 μM) alone increased and EHNA (1 μM) decreased alone, and their combination increased the potency of histamine to increase the FOC in H 2 -TG indicating that PDE3 and PDE4 regulate the inotropic effects of histamine in H 2 -TG. The PDE inhibitors (EHNA, cilostamide, rolipram) alone did not alter the potency of histamine to increase the heart beat in H 2 -TG whereas a combination of rolipram, cilostamide, and EHNA, or of rolipram and EHNA increased the potency of histamine to act on the beating rate. In summary, the data suggest that the PCE of histamine in H 2 -TG atrium involves PDE 2 and 4 activities, whereas the PIE of histamine are diminished by activity of PDE 3 and 4.

Macrofauna as a major driver of bentho‐pelagic exchange in the southern North Sea - Andreas Neumann; Justus E. E. van Beusekom; Annika Eisele; Kay‐Christian Emeis; Jana Friedrich; Ingrid Kröncke; Ella Lu Logemann; Julia Meyer; Céline Naderipour; Ulrike Schückel; Alexa Wrede; Michael L. Zettler (Limnology and Oceanography, 2021)
The contribution of sediments to nutrient cycling of the coastal North Sea is strongly controlled by the intensity of fluxes across the sediment water interface. Pore‐water advection is one major exchange mechanism that is well described by models, as it is determined by physical parameters. In contrast, biotransport (i.e., bioirrigation, bioturbation) as the other major transport mechanism is much more complex. Observational data reflecting biotransport, from the German Bight for example, is scarce. We sampled the major sediment provinces of the German Bight repeatedly over the years from 2013 to 2019. By employing ex situ whole core incubations, we established the seasonal and spatial variability of macrofauna‐sustained benthic fluxes of oxygen and nutrients. A multivariate, partial least squares analysis identified faunal activity, in specifically bioturbation and bioirrigation, alongside temperature, as the most important drivers of oxygen and nutrient fluxes. Their combined effect explained 63% of the observed variability in oxygen fluxes, and 36–48% of variability in nutrient fluxes. Additional 10% of the observed variability of fluxes were explained by sediment type and the availability of plankton biomass. Based on our extrapolation by sediment provinces, we conclude that pore‐water advection and macrofaunal activity contributed equally to the total benthic oxygen uptake in the German Bight.

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: the importance of private collections - Carolin Haug; Jelle W. F. Reumer; Joachim T. Haug; Antonio Arillo; Denis Audo; Dany Azar; Viktor Baranov; Rolf Beutel; Sylvain Charbonnier; Rodney Feldmann; Christian Foth; René H. B. Fraaije; et al. (PalZ, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Dead urchin walking: resilience of an arctic Strongylocentrotus to severe skeletal damage - Max Wisshak; Christian Neumann (Polar Biology, 2020)
The ability of bottom-dwelling marine fauna to repair injured body parts is critical to the survival of individuals from disturbances that inflict wounds. The phylum Echinodermata, in particular, exposes a pronounced ability to regenerate skeletal damages. Regeneration of lost body parts of stellate echinoderms (crinoids, asteroids and ophiuroids) is a well-documented phenomenon, whereas sea urchins (echinoids) have received much less attention. Here we report, for the first time, a field observation on an adult sea urchin of the genus Strongylocentrotus in its natural habitat, exposing severe skeletal damage but remarkable survivorship. The sea urchin was revealed by analysing a time series of seafloor images taken during a lander deployment in a rhodolith bed in the polar waters of northern Spitsbergen, Svalbard. Despite the loss of half the aboral region of the test, including existential organs, the sea urchin continued to move across the seafloor for more than 43 h, thereby escaping another predation attack by a large crab. The observed behaviour is grounded in the peculiarity of the sea urchins’ nervous system where locomotion is controlled by a decentralised ectoneural system in the epithelium, large parts of which had remained intact after the traumatic event. Our field observation thus documents initial post-traumatic survival of severe lesions, which is a basic prerequisite for beginning repair processes.

Reducing negative affect with anodal transcranial direct current stimulation increases memory performance in young—but not in elderly—individuals - Jessica Peter; Elisabeth Neumann-Dunayevska; Franziska Geugelin; Nadia Ninosu; Christian Plewnia; Stefan Klöppel (Brain Structure and Function, 2019)

Assessment of Uncertainties in Scenario Simulations of Biogeochemical Cycles in the Baltic Sea - H. E. Markus Meier; Moa Edman; Kari Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2019)

Assessment of Eutrophication Abatement Scenarios for the Baltic Sea by Multi-Model Ensemble Simulations - H. E. Markus Meier; Moa K. Edman; Kari J. Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2018)

Weitschataster intermedius gen. et sp. nov., a goniasterid starfish (Echinodermata: Asteroidea) from the Upper Cretaceous of Germany - Christian Neumann; Peter Girod (PalZ, 2018)

New long-horned caddisflies in Eocene Baltic amber (Insecta, Trichoptera) - Wilfried Wichard; Christian Neumann; Ingmar Werneburg (PalZ, 2018)

Effect of ultraviolet photofunctionalization of dental titanium implants on osseointegration - Christian Mehl; Matthias Kern; Friederike Neumann; Telse Bähr; Jörg Wiltfang; Volker Gassling (Journal of Zhejiang University-SCIENCE B, 2018)

Hydrogeologische Erkundung von Grundwasser in der ariden und vulkanisch aufgebauten Westkordillere Boliviens - Christian Neumann-Redlin; Rodolfo Huaranca Olivera (Grundwasser, 2018)

Rediscovery of type material of the bioerosional trace fossil Talpina von Hagenow, 1840 and its ichnotaxonomic implications - Max Wisshak; Christian Neumann; Dirk Knaust; Mike Reich (PalZ, 2017)

Y-P30 promotes axonal growth by stabilizing growth cones - Janine R. Neumann; Suvarna Dash-Wagh; Kay Jüngling; Teresa Tsai; Martin Meschkat; Andrea Räk; Sabine Schönfelder; Christian Riedel; Mohammad I. K. Hamad; Stefan Wiese; Hans-Christian Pape; Kurt Gottmann; et al. (Brain Structure and Function, 2015)

Echoes from the Past: A Healthy Baltic Sea Requires More Effort - Aarno T. Kotilainen; Laura Arppe; Slawomir Dobosz; Eystein Jansen; Karoline Kabel; Juha Karhu; Mia M. Kotilainen; Antoon Kuijpers; Bryan C. Lougheed; H. E. Markus Meier; Matthias Moros; Thomas Neumann; et al. (Ambio, 2014)

Small Hive Beetles are Facultative Predators of Adult Honey Bees - Christian W. W. Pirk; Peter Neumann (Journal of Insect Behavior, 2013)

Microbial communities along biogeochemical gradients in a hydrocarbon‐contaminated aquifer - Karolin Tischer; Sabine Kleinsteuber; Kathleen M. Schleinitz; Ingo Fetzer; Oliver Spott; Florian Stange; Ute Lohse; Janett Franz; Franziska Neumann; Sarah Gerling; Christian Schmidt; Eyk Hasselwander; et al. (Environmental Microbiology, 2013)
Summary Micro‐organisms are known to degrade a wide range of toxic substances. How the environment shapes microbial communities in polluted ecosystems and thus influences degradation capabilities is not yet fully understood. In this study, we investigated microbial communities in a highly complex environment: the capillary fringe and subjacent sediments in a hydrocarbon‐contaminated aquifer. Sixty sediment sections were analysed using terminal restriction fragment length polymorphism ( T‐RFLP ) fingerprinting, cloning and sequencing of bacterial and archaeal 16 S rRNA genes, complemented by chemical analyses of petroleum hydrocarbons, methane, oxygen and alternative terminal electron acceptors. Multivariate statistics revealed concentrations of contaminants and the position of the water table as significant factors shaping the microbial community composition. Micro‐organisms with highest T‐RFLP abundances were related to sulphate reducers belonging to the genus D esulfosporosinus , fermenting bacteria of the genera S edimentibacter and S mithella , and aerobic hydrocarbon degraders of the genus A cidovorax . Furthermore, the acetoclastic methanogens M ethanosaeta , and hydrogenotrophic methanogens M ethanocella and M ethanoregula were detected. Whereas sulphate and sulphate reducers prevail at the contamination source, the detection of methane, fermenting bacteria and methanogenic archaea further downstream points towards syntrophic hydrocarbon degradation.

Integrated methodology for assessing the HCH groundwater pollution at the multi-source contaminated mega-site Bitterfeld/Wolfen - Peter Wycisk; Reiner Stollberg; Christian Neumann; Wolfgang Gossel; Holger Weiss; Roland Weber (Environmental Science and Pollution Research, 2013)

In-Lake Neutralization: Quantification and Prognoses of the Acid Load into a Conditioned Pit Lake (Lake Bockwitz, Central Germany) - Kai-Uwe Ulrich; Christian Bethge; Ina Guderitz; Ben Heinrich; Volker Neumann; Claus Nitsche; Friedrich-Carl Benthaus (Mine Water and the Environment, 2012)

Impact of Climate Change on Ecological Quality Indicators and Biogeochemical Fluxes in the Baltic Sea: A Multi-Model Ensemble Study - H. E. Markus Meier; Bärbel Müller-Karulis; Helén C. Andersson; Christian Dieterich; Kari Eilola; Bo G. Gustafsson; Anders Höglund; Robinson Hordoir; Ivan Kuznetsov; Thomas Neumann; Zohreh Ranjbar; Oleg P. Savchuk; et al. (Ambio, 2012)

Raman study of apatite amorphised with swift heavy ions under various irradiation conditions - Christian Weikusat; Ulrich A. Glasmacher; Beatrice Schuster; Christina Trautmann; Ronald Miletich; Reinhard Neumann (Physics and Chemistry of Minerals, 2011)

Heavy-ion irradiation on crystallographically oriented cordierite and the conversion of molecular CO2 to CO: a Raman spectroscopic study - Christian Weikusat; Ronald Miletich; Ulrich A. Glasmacher; Christina Trautmann; Reinhard Neumann (Physics and Chemistry of Minerals, 2010)

Short-sighted evolution of virulence in parasitic honeybee workers (Apis mellifera capensis Esch.) - Robin F. A. Moritz; Christian W. W. Pirk; H. Randall Hepburn; Peter Neumann (The Science of Nature, 2008)

Nestmate recognition for eggs in the honeybee (Apis mellifera L.) - Christian W. W. Pirk; Peter Neumann; Randall Hepburn (Behavioral Ecology and Sociobiology, 2007)

Holocene vegetation and climate history of the northern Golan heights (Near East) - Frank Neumann; Christian Schölzel; Thomas Litt; Andreas Hense; Mordechai Stein (Vegetation History and Archaeobotany, 2007)

Holocene vegetation and climate history of the northern Golan heights (Near East) - Frank Neumann; Christian Schölzel; Thomas Litt; Andreas Hense; Mordechai Stein (Vegetation History and Archaeobotany, 2007)

Seasonal nestmate recognition in the ant Formica exsecta - Andreas Katzerke; Peter Neumann; Christian W. W. Pirk; Peter Bliss; Robin F. A. Moritz (Behavioral Ecology and Sociobiology, 2006)

Mutations of the SDHB and SDHD genes - Christian Pawlu; Birke Bausch; Hartmut P. H. Neumann (Familial Cancer, 2005)

Dritter ICA Mountain Cartography Workshop vom 15. bis 19. Mai 2002 am Mount Hood, Oregon, USA - Tobias Dahinden; Christian Häberling; Bernhard Jenny; Andreas Neumann; Stefän Räber; Lorenz Hurni (KN - Journal of Cartography and Geographic Information, 2004)

Coulonia parva n. sp., a new species of Astropectinidae (Asteroidea; Echinodermata) from the Santonian (Upper Cretaceous) of Sierra de Montsech (southern Pyrenees, Spain) - Christian Neumann; Hans Hess (PalZ, 2001)

Combined space-variant maps for optical-flow-based navigation - Gregory Baratoff; Christian Toepfer; Heiko Neumann (Biological Cybernetics, 2000)

Niederländisch-Deutscher Kartographiekongress/48. Deutscher Kartographentag in Maastricht, 17.–20. Mai 1999 - Joachim Neumann; Gudrun K. Zögner; Miroslav Mikšovský; Christian Häberling (KN - Journal of Cartography and Geographic Information, 1999)